Dry needling is effective in reducing acute pain in patients with severe knee osteoarthritis - Antonio, Amanda Machado; Gaspardi, Thaina Cristina Vieira; Couto, Evelyn Regina; de Campos, Gustavo Constantino; de Miranda, João Batista; Zorzi, Alessandro Rozim (International Journal of Clinical Trials, 2020)
Background: The objectives of the study was to evaluate the efficacy of dry needling inactivation of trigger points in acute pain relief and function improvement in patients with severe knee osteoarthritis. Methods: Thirty participants choose between dry needling or static stretching. It was analyzed the immediate effects of a single dry needling intervention, compared to a control group that received static stretching. Outcomes of the study was timed up and go test; visual analogue scale and brief pain inventory. Results: The group treated with dry needling had a better result on the visual analogue scale and on the brief pain inventory scale. There was no difference in time up and go performance in relation to the control group. The muscle group with the highest prevalence of trigger points was the thigh adductors (83.3%), despite valgus or varus frontal plane misalignment of the limb. Conclusions: The inactivation of trigger points by dry needling in patients with acute pain due to severe osteoarthritis of the knees obtained better relief compared to static stretching of the musculature.